Adding to Yersinia enterocolitica Gene Pool Diversity: Two Cryptic Plasmids from a Biotype 1A Isolate. (6th September 2009) - Lepka, Daniela; Kerrinnes, Tobias; Skiebe, Evelyn; Hahn, Birgitt; Fruth, Angelika; Wilharm, Gottfried
Abstract : We report the nucleotide sequence of two novel cryptic plasmids (4357 and 14 662 base pairs) carried by a Yersinia enterocolitica biotype 1A strain isolated from pork. As distinguished from most biotype 1A strains, this isolate, designated 07-04449, exhibited adherence to eukaryotic cells. The smaller plasmid pYe4449-1 carries five attributable open reading frames (ORFs) encoding the first CcdA/CcdB-like antitoxin/toxin system described for a Yersinia plasmid, a RepA-like replication initiation protein, and mobilizing factors MobA and MobC. The deduced amino acid sequences showed highest similarity to proteins described in Salmonella (CcdA/B), Klebsiella (RepA), and Plesiomonas (MobA/C) indicating genomic fluidity among members of the Enterobacteriaceae . One additional ORF with unknown function, termed ORF5, was identified with an ancestry distinct from the rest of the plasmid. While the C+G content of ORF5 is 38.3%, the rest of pYe4449-1 shows a C+G content of 55.7%. The C+G content of the larger plasmid pYe4449-2 (54.9%) was similar to that of pYe4449-1 (53.7%) and differed from that of the Y. enterocolitica genome (47.3%). Of the 14 ORFs identified on pYe4449-2, only six ORFs showed significant similarity to database entries. For three of these ORFs likely functions could be ascribed: a TnpR-like resolvase and a phage replication protein, localized each on a low C+G island, and DNA primase TraC. Two ORFs of pYe4449-2, ORF3 and ORF7, seem to encode secretable proteins. Epitope-tagging of ORF3 revealed protein expression at4 ° C but not at or above27 ° C suggesting adaptation to a habitat outside swine. The hypothetical protein encoded by ORF7 is the member of a novel repeat protein family sharing theDxxGN(x) n DxxGN motif. Our findings illustrate the exceptional gene pool diversity within the species Y. enterocolitica driven by horizontal gene transfer events.